2016
DOI: 10.17051/io.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Zihinden Hesaplama Yaparken Kullandıkları Stratejiler

Abstract: ÖZ. Bu araştırmanın amacı ortaokul beşinci sınıf öğrencilerinin toplama-çıkarma işlemi yaparken kullandıkları ve tercih ettikleri ideal zihinden hesaplama stratejilerini belirlemektir. Nitel araştırma modellerinden özel durum çalışmasına göre desenlenen bu araştırma, 2014-2015 öğretim yılının güz döneminde gerçekleştirilmiştir. Araştırma, bir devlet ortaokulunda öğrenim gören 16'sı erkek 17'si kız olmak üzere toplam 33 beşinci sınıf öğrencisiyle gerçekleştirilmiştir. Araştırmanın verileri araştırmacılar tarafı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Another result of this study is that pre-service teachers use mostly the strategies of "adding by separating the number into decades and ones" and "rounding off the number to the nearest decimal". This finding is also compatible with the literatüre (Aydın Güç & Hacısalihoğlu Karadeniz 2016;Çelikkol, 2022;Çibir & Yazgan, 2021;Duran et al, 2016). Considering that these two strategies are more emphasized in the mathematical curriculum and that these two strategies are better comprehended by the pre-service teachers, this can be seen as a positive result.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Another result of this study is that pre-service teachers use mostly the strategies of "adding by separating the number into decades and ones" and "rounding off the number to the nearest decimal". This finding is also compatible with the literatüre (Aydın Güç & Hacısalihoğlu Karadeniz 2016;Çelikkol, 2022;Çibir & Yazgan, 2021;Duran et al, 2016). Considering that these two strategies are more emphasized in the mathematical curriculum and that these two strategies are better comprehended by the pre-service teachers, this can be seen as a positive result.…”
Section: Discussionsupporting
confidence: 83%
“…This result is important in terms of showing that pre-service teachers use a small number of strategies. Parallel findings were presented in the other research (Duran, Doruk & Kaplan, 2016;Reys, Reys, Nohda & Emori, 1995). Another result of this study is that pre-service teachers use mostly the strategies of "adding by separating the number into decades and ones" and "rounding off the number to the nearest decimal".…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Huang and Yang (2018) studied the strategies used by 4th graders when solving questions necessitating number sense, and found that children used rulebased strategies, but middle and low-level children were more inclined to use these strategies. However, in a noteworthy study by Duran et al, (2016) focusing on the mental calculation strategies of middle school fifth graders when adding and subtracting, it was found that students did not use any strategy correctly and could not answer the questions.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Regarding the topic of the present study, Aydın Güç and Hacısalihoğlu Karadeniz (2016) found that the most common strategy used by 5th graders during mental addition is the strategy of adding by using the change and merge feature of addition, and the least commonly used one is to break the numbers based on multiples of 10. Similarly, Duran et al, (2016) reported that the most common strategy among middle school students was "adding by dividing into tens and ones" while the least used one was "breaking down the numbers by taking 10 as reference".…”
Section: Related Studiesmentioning
confidence: 99%